2019
DOI: 10.1186/s12984-019-0528-6
|View full text |Cite
|
Sign up to set email alerts
|

Deficits in tapping accuracy and variability in tremor patients

Abstract: Background The basal ganglia and cerebellum are brain structures involved in movement initiation, execution and termination. They are thought to be involved in the tremor generation and movement deficits in Parkinson’s disease (PD) and essential tremor (ET). Especially in PD, maintaining cyclic movement, such as walking or tapping can be significantly disturbed. Providing external cues improves timing of these movements in PD but its effect on ET has not yet been studied in depth. The aim of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…This study focused on motor symptoms of the upper limb using a flexible sensor on the hand, but other sensor placements may be relevant for monitoring global presentations of symptoms. Incorporating additional types of sensors may improve detection accuracy, such as utilizing EMG data in tremor classification [36]. Note that the optimal data collection strategy may vary for other symptoms of PD (e.g., freezing of gait, postural instability, muscle rigidity, dystonia).…”
Section: Discussionmentioning
confidence: 99%
“…This study focused on motor symptoms of the upper limb using a flexible sensor on the hand, but other sensor placements may be relevant for monitoring global presentations of symptoms. Incorporating additional types of sensors may improve detection accuracy, such as utilizing EMG data in tremor classification [36]. Note that the optimal data collection strategy may vary for other symptoms of PD (e.g., freezing of gait, postural instability, muscle rigidity, dystonia).…”
Section: Discussionmentioning
confidence: 99%
“…The frontal area is mainly responsible for motor planning, organization and regulation and is involved in initiation, maintenance, coordination and planning of complex sequences of movements. In most cases the HC group had a significantly higher TRP in this region indicating that these areas are important for a high tapping accuracy [2]. In the posterior area, areas responsible for combining somatosensory, auditory and visual information and also areas that are involved in motor learning and bimanual manipulation are located.…”
Section: Intra-groups Analysis Healthy Controlsmentioning
confidence: 92%
“…The percentage of tremor presence during each task was determined for each subject by calculating the percentage of epochs in which kinetic tremor was detected. From the accelerometer data the tapping accuracy [2] was calculated for each task and tapping condition according to (4).…”
Section: Outcome Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have investigated movement parameters and cortical and subcortical changes in patients and healthy controls during hand and finger movements. In a previous study [89] we showed that PD patients tap significantly less accurately during a 2 Hz tapping task and with a greater variability during a 4 Hz tapping task than ET patients and healthy controls (HC). Furthermore, ET patients tapped less accurately and with a greater variability than HC during a 4 Hz tapping task.…”
Section: Introductionmentioning
confidence: 96%